PENGARUH DISKON DAN PROMO TERHADAP KEPUTUSAN PEMBELIAN DI KALANGAN GENERASI MUDA - Amanda Talitha Fitri; Yusniar; Ramadhan Aditya Putra; Evi Syuriani Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of discounts and promotions on purchasing decisions among young consumers. This research uses a qualitative approach with a library research method by reviewing various scientific literature such as books, academic journals, and previous studies relevant to the topic. The data used are secondary data obtained from academic sources discussing marketing strategies, consumer behavior, and purchasing decision factors. The results show that discounts positively influence purchasing decisions by increasing perceived value and attracting consumer attention through lower prices. Promotions also have a significant role as marketing communication tools that enhance consumer awareness and build brand image. Furthermore, the combination of discounts and promotions is more effective in increasing product attractiveness and encouraging purchasing decisions among young consumers. As digital consumers, young people are highly responsive to marketing strategies that offer economic benefits and engaging shopping experiences. Therefore, integrating discounts and promotions is an effective strategy to improve purchasing decisions.